Re-assessing vulnerability to foodborne illness: pathways and practices. Issue 1 (1st January 2018) - Jackson, Peter; Meah, Angela
Abstract: Foodborne illness is a major public health concern, often approached by focusing on socio-demographic groups who are considered most 'vulnerable' to foodborne disease such as elderly people or pregnant women. Based on a review of existing literature and original research with UK consumers, this paper proposes an alternative approach to analysing vulnerability to foodborne illness. Challenging conventional approaches that focus on the inherent vulnerability of particular socio-demographic groups, the paper emphasises the context-specific and situational nature of vulnerability and the practices and pathways through which people negotiate specific threats which may, in turn, affect their future vulnerabilities. The paper also addresses the gap between lay and expert knowledge that may increase exposure to particular food-related risks. Evidence is provided from research on the food safety and health implications of consumers' everyday domestic practices including behaviours that do not comply with current 'best practice' advice. The evidence supports a turn from notions of inherent vulnerability, based on the membership of certain socio-demographic groups, towards a more nuanced understanding of situational vulnerability, based on the context and logic informing specific social practices.